2018
DOI: 10.1136/jclinpath-2018-205393
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic predictive value of Xpert Bladder Cancer Monitor in the follow-up of patients affected by non-muscle invasive bladder cancer

Abstract: AimsCystoscopy and urine cytology represent the gold standard for monitoring superficial bladder cancer (BC). Xpert BC Monitor is a new urinary marker based on the evaluation of five target mRNAs overexpressed in patients with bladder cancer. The aim of our study was to evaluate the diagnostic accuracy of Xpert BC Monitor in follow-up of patients with non-muscle invasive bladder cancer (NMIBC).Methods230 patients were included in this prospective study. Xpert BC Monitor cut-off was set to 0.5. Sensitivity, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
8
24
0
Order By: Relevance
“…The XPert ® Bladder Cancer (BC) Monitor (Cepheid, Sunnyvale, CA, USA) is a RT-PCR test that measures the number of urinary transcripts in five genes, UPK1B , IGF2 , CRH , ANXA10, and ABL1 , and was designed for BCa patient follow-up [ 77 ]. This test was superior to cytology on NMIBC during follow-up, in terms of sensitivity (84% versus 33%), while presenting similar specificity (91% versus 94%) [ 77 ], despite controversial findings from another study, that indicated 46.7% sensitivity and 77% specificity [ 114 ]. The heterogeneity between studies and the lack of external validation makes its present use unreliable.…”
Section: Liquid Biopsy As a Source Of Biomarkers For Bladder Cancementioning
confidence: 99%
“…The XPert ® Bladder Cancer (BC) Monitor (Cepheid, Sunnyvale, CA, USA) is a RT-PCR test that measures the number of urinary transcripts in five genes, UPK1B , IGF2 , CRH , ANXA10, and ABL1 , and was designed for BCa patient follow-up [ 77 ]. This test was superior to cytology on NMIBC during follow-up, in terms of sensitivity (84% versus 33%), while presenting similar specificity (91% versus 94%) [ 77 ], despite controversial findings from another study, that indicated 46.7% sensitivity and 77% specificity [ 114 ]. The heterogeneity between studies and the lack of external validation makes its present use unreliable.…”
Section: Liquid Biopsy As a Source Of Biomarkers For Bladder Cancementioning
confidence: 99%
“…7,18 In contrast, the study performed by Elia et al reported an overall sensitivity of only 46.2% for the XBC, though the vast majority (87%) of the detected bladder tumours in that study were low-grade. 19 In our study, none of the patients with negative XBC had a positive VUC, therefore complementing the results of the XBC with VUC did not increase sensitivity, specificity, NPV, or PPV, which was also observed in the study by Pichler et al 7 Until more studies on the XBC have been conducted, the range of sensitivities and NPVs cannot be estimated, though our data and already published studies 7,18 show that the performance of the XBC is at least comparable to previously studied bladder cancer biomarkers for which studies have reported wide variability in performance. A recent review of bladder cancer biomarkers summarized data from several studies listing the sensitivities of NMP22 in the range of 24% to 81%, of BTA STAT 40% to 72%, of ImmunoCyt 50% to 85%, and of UroVysion 13 to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the Bladder EpiCheck test with other bladder tumor markers, it is superior to the Bladder Xpert Monitor, 18 nuclear matrix protein 22 (NMP 22) testing, the bladder tumor antigen (BTA) test, 19 or fluorescence in situ hybridization, 20 whereas cytology is more specific 18 (see also Grossman et al 21 ). In terms of sensitivity, specificity, and NPV, it performs very well with an area under the curve of 0.785.…”
Section: Discussionmentioning
confidence: 99%